THE PROCESS OF CARDIAC REMODELING IN PATIENTS WITH CHRONIC HEART FAILURE COMPLICATED BY RENAL DYSFUNCTION - Aliqulov I.T; Yusupova M.Sh; Sultanova F.T (Western European Studies, 2025)
Chronic heart failure (CHF) remains the most common, severe, and adverse complication of cardiovascular diseases. In all developed countries, the issue of CHF prevalence is becoming increasingly significant every year.
Keywords: chronic heart failure; renal dysfunction; cardiac remodeling